Capitalismo y subjetividad: el sujeto como trabajador en el discurso filosófico de la modernidad europea (2011)
The problem of labor is remarkably present in many of the current debates that, from a philosophical and a social sciences perspective, endeavor to elucidate the transformations experienced in the dynamics of Capitalism. However, these discussions seem to ignore the need for this concept to be defined in its specificity. Assuming Karl Marx´s Labor Theory of Value, this paper aims to bring up some issues that, in our opinion, should be considered in a genealogical - conceptual approach to the ways of human labor in capitalist production, particularly in what refers to subjectification. To reach this objective we will concentrate on the philosophical discourse of the european Modernity, focusing on its canonic version, meaning to compose some relations between the concepts articulated by that discourse and the ways that Capitalisms has adopted throughout its historical becoming.